THE QUANTITATIVE ASSESSMENT OF SPITAK EARTHQUAKE AFTERSHOCK STAGE (Proceedings of the YSU C: Geological and Geographical Sciences, 2006)
In this paper the quantitative assessment of aftershocks distribution for the Spitak earthquake in 1988 with magnitude M=7.0 is presented, to define the catalogue of declusterisation parameters. Comparing the released summary energy and earthquakes number before the main shock quiescence period with the same period after aftershocks, the aftershocks' real continuation period has been assessed. Received results for selected area has been compared with empirical equations of Omari and Utsu-Seki.
Keywords: Omari; Utsu-Seki; aftershocks’ real continuation period; Spitak earthquake; declusterisation parameters